2017
DOI: 10.1016/j.physbeh.2016.12.041
|View full text |Cite
|
Sign up to set email alerts
|

Stress coping style does not determine social status, but influences the consequences of social subordination stress

Abstract: Access to the full text of the published version may require a subscription. This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…This hypothesis might explain why these subjects had higher corticosterone levels than AA and PR mice after the first stressful interaction. Thus, the findings would support the hypothesis that coping styles influence the outcome of experienced stress due to social subordination (Boersma et al, 2017). Although corticosterone levels were approximately equal in all stressed groups after nine days of stress, we cannot exclude that a long-term effect on other components of the HPA axis and/or on other physiological variables related to the function of the HPA axis (brain-derived neurotrophic factor, immune system, etc.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…This hypothesis might explain why these subjects had higher corticosterone levels than AA and PR mice after the first stressful interaction. Thus, the findings would support the hypothesis that coping styles influence the outcome of experienced stress due to social subordination (Boersma et al, 2017). Although corticosterone levels were approximately equal in all stressed groups after nine days of stress, we cannot exclude that a long-term effect on other components of the HPA axis and/or on other physiological variables related to the function of the HPA axis (brain-derived neurotrophic factor, immune system, etc.…”
Section: Discussionmentioning
confidence: 55%
“…The physiological and behavioral responses to acute stress can be adaptive, but exposure to chronic stress, particularly chronic psychosocial stress, can have negative consequences and increase susceptibility to chronic diseases, including depression (Hollis, Isgor, & Kabbaj, 2013) and cancer (Sommershof, Scheuermann, Koerner, & Groettrup, 2017). One of the most common chronic stressors in humans and other social animals is stress emerging from social interactions (Boersma et al, 2017;Brown, 2002;Kessler, 1997). Thus, losses of social rank, status and/or control are examples of chronic stressors that are increasingly recognized as risk factors for depression (Gotlib & Hammen, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…109,110 The vast majority of mixed-sex colony studies analyzing spontaneous agonistic encounters within a colony have revealed that strict, despotic social hierarchies are readily established among male rats and mice, while no hierarchies are observed among female rats and mice. [5][6][7][8]15,17,25,26,86,87,[111][112][113][114][115][116][117][118][119][120][121][122][123][124][125][126][127][128][129] In contrast, female hamsters housed in mixed-sex pairs establish strong dominant-subordinate relationships, with females typically maintaining dominance over the male. 130 However, a resident-intruder study using mixed-sex colonies of Long Evans rats has demonstrated that one male and one female in each colony exhibit social dominance evidenced by increased aggression toward an intruder rat introduced to the colony.…”
Section: Agonistic Behaviorsmentioning
confidence: 99%
“…As in same‐sex studies, social rank can be determined by analyzing the spontaneous agonistic behaviors among the colony members 6,29,105‐108 or the agonistic behaviors of colony members toward a stranger, “intruder” rodent in a resident‐intruder test 109,110 . The vast majority of mixed‐sex colony studies analyzing spontaneous agonistic encounters within a colony have revealed that strict, despotic social hierarchies are readily established among male rats and mice, while no hierarchies are observed among female rats and mice 5‐8,15,17,25,26,86,87,111‐129 . In contrast, female hamsters housed in mixed‐sex pairs establish strong dominant‐subordinate relationships, with females typically maintaining dominance over the male 130 .…”
Section: Agonistic Behaviorsmentioning
confidence: 99%